FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PASIEN RAWAT INAP DI PUSKESMAS - Listiono, Heru; Irdan, Irdan (JURNAL KESEHATAN TERAPAN, 2021)
Background: Puskesmas is an organization in which there are professional medical personnel and permanent health facilities that provide health services, ongoing care, diagnosis and treatment of diseases suffered by patients. Objective: To determine the factors associated with inpatient satisfaction at the Puskesmas. Methods: This study used an analytical survey with a cross sectional study design to see the instantaneous relationship between the independent and dependent variables. The sampling technique used was accidental sampling or accidental sampling in the field, with a sample size of 95 people. Result: after being selected with other independent variables, it still has a statistically significant relationship, where: OR: 3.066 (95% CI: 1.262-7.451) p = 0.013, giving an interpretation that patients who stated their response were not good had a tendency of 3.066 times to feel they were not. satisfied with the service compared with patients who expressed good response, after being selected with the empathy variable. Suggestion: It is necessary to improve the quality of service to patients, especially in the aspect of responsiveness and empathy of officers in order to increase patient satisfaction with health services.Key words : Inpatient Satisfaction